Independent Atelier Model: Supporting Preschool Education and Functional Requirements - Şahin, Belkıs Ece; DOSTOĞLU, NESLİHAN (My University, 2016)
Independent atelier model is defined in a doctoral dissertation, where the potential of an independent education environment is analyzed for equality in preschool education, completed by B. Ece Şahin at Uludağ University Department of Architecture, under the supervision of Prof. Dr. Neslihan Dostoğlu. Ateliers are described as small education places in city or natural environment where students can be attend different activities. Regard with the problem of not all children have the same educational opportunities in preschool education due to economic inadequacies, the model is accepted a solution which supporting the education in a short term. In this study, the assessments on ateliers’s functions are presented. It was interviewed with 30 children of age 5, their parents and teachers, in three public kindergartens in Bursa. These interviews have indicated that nine different functions which are ranch, science-nature, food growing- kitchen, drama, music-dance, art, technology, healthy living, making wooden toys for ateliers. These functions should consider important for meeting the requirements of education program in new education building’s designs.

Bağımsız atölye modeli, okulöncesi eğitim sürecinde eşit eğitim olanağı sunabilmek için bağımsız bir eğitim mekânının potansiyelinin sorgulandığı, B. Ece ŞAHİN tarafından, Neslihan Dostoğlu danışmanlığında Uludağ Üniversitesi Mimarlık Bölümü’nde tamamlanan doktora tezinde tanımlanmıştır. Kent ya da doğal çevrede yer alması önerilen atölyeler, anaokulu ve anasınıfı öğrencilerinin farklı etkinliklere katıldıkları küçük ölçekli eğitim mekânları olarak önerilmektedir. Ekonomik yetersizlikler sebebiyle okulöncesi eğitimden tüm çocukların eşit ölçüde yararlanamaması sorunu karşısında, bağımsız atölye modelinin eğitim sürecine kısa vadede destek verecek bir yaklaşım olduğu kabul edilmektedir. Bu çalışmada atölyelerin işlevlerinin belirlenmesine ilişkin değerlendirmeler sunulmaktadır. Bursa’da üç resmi bağımsız anaokulunda, 5 yaş grubunda eşit sayıda kız ve erkek olmak üzere toplam 30 çocuk, velileri ve öğretmenlerinin katılımıyla gerçekleştirilen çalışmada; çiftlik, bilim-doğa, gıda yetiştirme-mutfak, drama, müzik-dans, sanat, teknoloji, sağlıklı yaşam, ahşap oyuncak yapımı olmak üzere 9 işlev belirlenmiştir. Tanımlanan işlevlere, yeni eğitim binalarının tasarım süreçlerinde eğitim programı gereksinimlerine cevap verebilmek açısından önem verilmelidir.
Bağımsız Atölye Modeli: Okulöncesi Eğitimin Desteklenmesi ve İşlevsel Gereksinimler
Keywords: Preschool Education; Independent Atelier; Education Space; Functional Requirements; Okulöncesi Eğitim; Bağımsız Atölye; Eğitim Mekanı; İşlevsel Gereksinimler